(untitled) (LACCEI, 2024)
The proposal is based on relating the TDABC cost and the marginal cost for a manufacturing plant, focused on production cost management. To do this, we will first establish the relationship of the resources towards the groups of auxiliary activities and groups of operational activities, separating them into staggered (fixed) costs and variable costs based on the product or service. Once this assignment is determined, we will distribute the groups of auxiliary and operational activities towards the product or service, duly separated into staggered costs and variable costs in such a way that each group of activities can be assigned based on an hourly rate based on the number of transactions according to the TDABC procedure. We will take into account that fixed costs are assigned based on a rate with restriction since it is a cost limited to a period, different from the variable cost which can be assigned based on the volume of production. With this, we hope to finally distribute the cost of each separate activity group in a staggered and variable cost to the product or service, based on man time, machine time or another transaction, depending on the activity or cost object to be determined.